The effect of acacia honey on hemorheological properties of blood: Preliminary reports - Teległów, Aneta; Benedyk-Lorens, Ewa; Łabuzek, Monika (Health Promotion & Physical Activity, 2025)
The effect of bee honey on the hemorheological properties of blood is an interesting issue from the perspective of natural medicine. A type of honey that enjoys great popularity in Poland is acacia honey, obtained from the nectar of robinia pseudoacacia (i.e. black locust). The aim of the study was to examine the effect of regular consumption of acacia honey for 2 weeks on the hemorheological properties of blood; hemorheology plays a key role in understanding physiological and pathological processes related to blood circulation. In the study, a group of women (n = 10) consumed 1 tablespoon of acacia honey daily for 2 weeks. Honey consumed regularly in moderate amounts (e.g., 1–2 teaspoons daily) can be a valuable addition to health-supporting diet. Fasting blood samples were collected from the participants at the beginning of the study and later after 2 weeks. After consuming acacia honey, statistically significant decrease was found in: MCH (p < 0.05), MCV (p < 0.05) and EI at shear stress 60.00 (p < 0.05). Statistically significant increase was found in: MPV (p < 0.05), PDW (p < 0.05). No significant changes were observed in other rheological parameters or glucose levels. This study is the first to report the effect of regular, short-term consumption of acacia honey on the hemorheological properties of blood, however, this topic still requires further research.